Challenges and Gifts of Teaching Luther in a Lutheran College1. Issue 2 (June 2017) - Jodock, Darrell
Abstract: This article examines what can be learned from teaching Luther to American college students. It reviews several ways in which college students benefit from studying Luther. The article suggests that identifying the "operating principles" in Luther's thought can help students more carefully discern the contemporary significance of his thought. After discussing some challenges encountered when teaching Luther to college students, the article ends with reflections on the theological significance of the college context. While Luther's discovery of a gracious God remains central, the college setting promotes a retrieval of several broader themes in Luther's thinking that have often been neglected by Lutherans: ongoing creation, wisdom, the Bible as "torah, " the suffering of God, and societal reform.